Exploring the mechanisms that underpin an effective community first aid response: a rapid realist review - Claire Maynard; Laura Sims; Matthew Booker (International Journal of First Aid Education)
Background Community First Aid (CFA) interventions aim to improve the capacity of a community to effectively respond to urgent and emergency health needs, by providing training, education or response services. With urgent and emergency services under sustained pressure, there is growing interest in understanding how targeted and tailored CFA interventions might help improve health outcomes and mitigate demand on the health system. Understanding the underlying mechanisms of effective CFA interventions can help optimise their design, delivery and evaluation. Methods We conducted a rapid realist review to explore how CFA interventions work, for whom, and in what settings. MEDLINE was searched for relevant peer-reviewed articles and search results supplemented with relevant grey literature and additional articles identified by the research team. Middle-range theory was drawn upon to help synthesise findings and formulate Context-Mechanism-Outcome configurations. Findings The majority of the 46 included articles focused on CFA training interventions. By drawing on the Theory of Planned Behaviour, we formulated mechanisms which either tackle the barriers communities face, or draw on inherent enabling characteristics of communities, to improve perceived behavioural control, attitudes and subjective norms related to intention to perform FA. Conclusion By understanding community needs and characteristics and how they influence effective CFA responses, FA training and education interventions can be targeted and tailored, ultimately improving the intention of communities to perform effective FA. Communities should be involved in the co-design of CFA interventions.